2006
DOI: 10.1007/s10811-006-9030-1
|View full text |Cite
|
Sign up to set email alerts
|

Can Kelp Extract (KELPAK®) be Useful in Seaweed Mariculture?

Abstract: The addition of low concentrations of commercial kelp extract (Ecklonia maxima: Kelpak R ) in addition to fertiliser has proven to be beneficial in agriculture. It triggers rooting in field crops, increases yields and has other useful effects, such as parasite reduction. Its efficacy has been attributed to the fact that Kelpak R is produced by a cold process, and is a high auxin/low cytokinin product. The aim of this study was to investigate if seaweeds (which do not have a root system) grown in culture system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…in all tested concentrations forming small red patches along the thalli. -Andersson et al (2006) examined the effects of Kelpak® commercial extract made from Ecklonia maxima (Osbeck) Papenfuss on the red alga Gracilaria gracilis (Stackhouse) Steentoft, Irvine, et Farnham cultivated in vitro and later experimentally in commercial cultivation to verify the effect of this extract on the growth of Ulva lactuca Linnaeus obtaining significant results on growth rate (control-2.8% d −1 and best treatment result-1:1.000 concentration 6.1% d −1 ). Different from our study, the extract was added to the seawater where the algae were being cultivated.…”
Section: Resultsmentioning
confidence: 99%
“…in all tested concentrations forming small red patches along the thalli. -Andersson et al (2006) examined the effects of Kelpak® commercial extract made from Ecklonia maxima (Osbeck) Papenfuss on the red alga Gracilaria gracilis (Stackhouse) Steentoft, Irvine, et Farnham cultivated in vitro and later experimentally in commercial cultivation to verify the effect of this extract on the growth of Ulva lactuca Linnaeus obtaining significant results on growth rate (control-2.8% d −1 and best treatment result-1:1.000 concentration 6.1% d −1 ). Different from our study, the extract was added to the seawater where the algae were being cultivated.…”
Section: Resultsmentioning
confidence: 99%
“…The culture of Ulva spp. in nutrient-rich water increases their protein content roughly 3 to 10 fold (Shpigel et al, 1999;Boarder & Shpigel, 2001;Robertson-Andersson, 2004;Robertson-Andersson et al, 2006). This enriched Ulva has subsequently been shown to improve growth in, for example H. tuberculata (Neori et al, 1998;Shpigel et al, 1999), H. discus hannai (Shpigel et al, 1999), and H. roei (Boarder & Shpigel, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ulva lactuca and G. gracilis for the mixed diet were obtained on the farm from a cultured stock grown in abalone and fish (turbot) effluent. These seaweeds grown in abalone and turbot effluent have considerably higher nitrogen content than seaweed collected from local seashores (RobertsonAndersson, 2004;Robertson-Andersson et al, 2006). Ulva lactuca grown in these systems has an average protein content of 33.4% when grown in abalone waste, and 36.6% when grown in turbot waste as opposed to 3.7-19.9% in wild U. lactuca (Robertson-Andersson, 2004).…”
Section: Dietsmentioning
confidence: 99%
“…The present study showed that dipping of the three color morphotypes of K. alvarezii for 30 min at the lower AMPEP concentrations of 0.01-0.1 g L −1 resulted in higher growth rates compared to the controls. The active compounds of the seaweed extract must be applied in small doses to be effective, as also claimed by Robertson-Anderson et al (2006). The proliferation of young multiple shoots of the three color morphotypes of K. alvarezii and the yellowish brown K. alvarezii, grown in a commercial nursery, after 10-14 days of field growth could be attributed to the presence of growth promoters which stimulated auxin-like activity which further promoted shoot growth.…”
Section: Discussionmentioning
confidence: 85%
“…A single dose of 1:2,500 concentration, or in combination with aquaculture effluent water was used for the growth of the green, abalone feed species Ulva in a pilot-scale, commercial evaluation (Robertson-Anderson et al 2006). In a previous study by the authors of this study, A. nodosum extract powder promoted early shoot formation in the tissue culture of three varieties of Kappaphycus (Hurtado et al 2009.…”
Section: Introductionmentioning
confidence: 94%